TRANSLATION OF INDONESIAN CULTURAL TERMS IN RAINBOW TROOPS NOVEL: INVESTIGATING TRANSLATION METHODS - Yesi Yesi (La Tansa Mashiro, 2022)
This study was conducted to analyze the translation methods of Indonesian Cultural Terms. It suggests that there are 8 translation methods including Word-for-word translation, Literal translation, Faithful translation, and Semantic translation, Adaptation Free translation, Idiomatic translation, and Communicative translation. A qualitative approach was applied in this study. The method for analyzing data is content analysis. Peer discussion and triangulation were applied to enhance the validation. The result of the translation method mostly uses literal translation with 32.29%. This proves that the Target Language (TL) still has many vocabulary deficiencies. The translator could not find equivalent cultural terms, then the translator had to borrow them from the Source Language (SL) as the translator could not find the equivalent of cultural terms from the original novel.